Biofuels and Sustainable Development in India: Evaluating Socio-Economic and Environmental Potential - Md Shakeb Khan, Prof. Akram Ahmad Khan; Dr. Ramla Fatma, Dr. Nitesh Thakur; Dilawar Hussain (Journal of Informatics Education and Research, 2025)
This paper explores the socio-economic potential of biofuels in India, emphasizing their role in enhancing rural development, creating employment opportunities, and reducing greenhouse gas emissions. Biofuel feedstocks, including first-generation (e.g., vegetable oils, corn), second-generation (e.g., agricultural residues, Jatropha), and third-generation (e.g., algal biomass), present various economic and environmental benefits. Despite India's reliance on imported oil, biofuels can provide renewable energy sources, promote rural income, and contribute to environmental sustainability. The study highlights the economic viability of biofuel production, which can increase farmers' incomes and stimulate rural economies, as well as the social impacts, including improved infrastructure and livelihoods in rural areas. Environmental benefits of biofuels include lower greenhouse gas emissions and reduced air pollutants, contributing to India’s commitments under the Paris Agreement. However, concerns over land use and food security remain significant. The paper suggests promoting second-generation biofuels and utilizing marginal lands for non-food crops to mitigate these issues. The development of biofuels in India represents a multi-faceted opportunity to address energy security, environmental sustainability, and socio-economic development. With the right policies and investments, biofuels can play a transformative role in India's energy landscape, contributing to sustainable development goals without compromising food security or environmental integrity.